2013
DOI: 10.1021/ie402363h
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of the Cyclic CO2 Injection Process in Light Oil Systems

Abstract: Performance of cyclic CO 2 injection as an enhanced oil recovery (EOR) technique in a light crude oil system was experimentally investigated. Series of cyclic CO 2 injection tests were designed and carried out at various operating conditions. Effects of parameters including operating pressure (P op ), injection time (t inj ), soaking period (t soaking ) and connate water saturation (S wc ) were investigated on the oil recovery factor (RF) of cyclic injection tests. First, the CO 2 solubility in the crude oil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Various studies have suggested that low IFTs between the injected fluid and oil reservoir can improve sweep efficiencies and reduce residual oil saturation. [17][18][19] In CO 2 -based EOR techniques, at a spe- cific thermodynamic conditions (i.e., pressure, temperature, and composition), the IFT of the crude oil-CO 2 system decreases to a sufficiently low values which leads to a more favorable displacing process. In this study, the axisymmetric drop shape analysis (ADSA) technique for the pendant drop case was applied to determine the IFT between the crude oil and CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have suggested that low IFTs between the injected fluid and oil reservoir can improve sweep efficiencies and reduce residual oil saturation. [17][18][19] In CO 2 -based EOR techniques, at a spe- cific thermodynamic conditions (i.e., pressure, temperature, and composition), the IFT of the crude oil-CO 2 system decreases to a sufficiently low values which leads to a more favorable displacing process. In this study, the axisymmetric drop shape analysis (ADSA) technique for the pendant drop case was applied to determine the IFT between the crude oil and CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[1] The performance of CO 2 -based EOR processes is mainly affected by the solubility of the CO 2 in the oil phase because it results in viscosity reduction and swelling. [1,2] CO 2 miscibility with oil can be achieved at a relatively high pressure and low temperature and only when the oil possesses a relatively high API gravity (higher than 36 8API). When injected at immiscible condition, the CO 2 enhances oil recovery through viscosity reduction, oil swelling, and solution gas drive mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, more oil can be produced and oil recovery can be enhanced by reducing oil viscosity, expanding oil volume, and extracting the light components of crude oil. [18][19][20][21][22][23] Mohammed-Singh et al 24 summarized the cases of CO 2 huff and puff in oil fields over the past two decades. Among above methods, CO 2 huff and puff has attracted more attention as an efficient and important technique.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Both soaking time and CO 2 injection volume are important operation parameters to improve the performance of CO 2 huff and puff. [18][19][20][21][22][23] Mohammed-Singh et al 24 summarized the cases of CO 2 huff and puff in oil fields over the past two decades. They found that the best soaking time was 2-4 weeks and massive CO 2 injection enhanced the oil recovery of CO 2 huff and puff.…”
Section: Introductionmentioning
confidence: 99%